Pazopanib in patients with primary multi-metastatic bone Ewing sarcoma - Raciborska, Anna; Bilska, Katarzyna; Węcławek-Tompol, Jadwiga; Sega-Pondel, Dorota; Zelwiańska, Anna; Przybyszewski, Borys; Chaber, Radosław; Tomaszewska, Renata; Antoniuk-Majchrzak, Justyna; Koziński, Tomasz (Frontiers in Oncology, 2025)
BackgroundDespite the use of different treatment regimens, patients with primary multi-metastatic Ewing sarcoma disease have a dismal outcome. Lately, pazopanib has been proposed as an effective salvage regimen for soft tissue sarcoma (STS), including extraosseous Ewing sarcoma (ESS). Thus, we sought to evaluate this approach for young patients with primary multi-metastatic bone Ewing sarcoma.Materials and methodsEleven patients with primary multi-metastatic bone Ewing sarcoma (metastasis to the bone and/or bone marrow), received standard first-line treatment in parallel with pazopanib. All patients had standard tumor imaging and laboratory evaluation. All toxicities were documented.ResultsPazopanib was administered throughout the whole treatment period (paused during the surgical procedure) and after its completion, on average 1.7 years (range 0.9 to 5.1). At the time of the beginning of pazopanib, the median age was 14.2 years (range 5.1 to 17.8 years). The primary tumor was operated on in five patients. Ten patients received concurrent radiation therapy, and 3 autologous hematopoietic stem cell transplantation. Significant toxicities have not been observed. One patient (9.1%) progressed. Two patients had relapse (18.2%), and one patient died (9.1%). Ten patients (90.9%) are alive with a median time follow-up 2.6 years (range 1.2 to 9.2 years). The estimated 2-year event-free survival and overall survival for the whole group were 68.2% and 85.7%, respectively.ConclusionsPazopanib was well-tolerated in young patients, even when it was administered with chemotherapy and radiation therapy together. Pazopanib turned out to be effective in patients with primary multi-metastatic Ewing sarcoma and particularly could be considered as an option for them. This regimen deserves further investigation.